A cultural psychological analysis of cultural change. Issue 1 (23rd November 2017) - Hamamura, Takeshi
Abstract : Life experience appears to be transforming in contemporary societies, with changes taking place in Asia being particularly substantial. There is strong public interest in understanding how these changes affect individual psyches. Scientific understanding of this issue, however, has not kept pace with change. Research findings from Western societies, the USA in particular, provide a model for understanding and predicting patterns of cultural change in Asia. However, the applicability of the model in this region requires critical examination. This article presents an overview of the available evidence in this research field, reviewing available psychological research that examines cultural change in the USA, China, Japan, and Australia. This paper's aim is to stimulate interest in this research area within the community of Asian social psychologists as our Asia‐based insights have much to contribute to the fundamental research question at stake, and the nature of the interplay between a changing social ecology, cultural environment, and participating psyches.